Development of passive sampling devices for bioavailable contaminants of current and emerging concern: Waitemata Harbour case study. Issue 4 (1st October 2016) - Stewart, M; Cameron, M; McMurtry, M; Sander, SG; Benedict, B; Graham, L; Hosie, M; Green, T
ABSTRACT: Bioavailable contaminant concentrations are an important component in assessing environmental effects as they directly affect ecosystem health. Shellfish contaminant monitoring programmes have traditionally filled this requirement but are being phased out in some jurisdictions. Passive sampling devices (PSDs) have the potential to replace shellfish monitoring; however, there are still knowledge gaps to address before this can occur. This study assessed the suitability of three different PSDs in providing the required information to replace shellfish monitoring. PSDs were deployed at three historic mussel monitoring sites with different levels of urban influence in the Waitemata Harbour, Auckland, New Zealand. Contaminants of interest were urban heavy metals, plus current and emerging organic contaminants. PSDs provided extremely low detection limits and, for some contaminants, very strong correlations to shellfish. PSDs can currently complement shellfish in monitoring, but it is premature to make conclusions as to the suitability of PSDs in replacing shellfish monitoring until more information is available.